Taxing deficits to restrain government spending and foster capital accumulation - Nikolai Stähler (Deutsche Bundesbank, 2007)
In a dynamic model of fiscal policy, social polarization provokes a deficit bias. Policy advisors have recently proposed that governments running a deficit should be forced to generate additional tax revenue. We show that this deficit taxation reduces the deficit bias as it internalizes the externality different lobby groups impose on others. The mechanism described here is not due to the political risk of being elected out of office because the private sector dislikes taxation. Lower government spending and the resulting reduced deficit bias augment capital accumulation.
Keywords: E62; H63; H62; H61; 330; fiscal rules; deficit taxation; polarization; capital accumulation; Finanzpolitik; Haushaltsdefizit; Steuerpolitik; Externer Effekt; Investition; Theorie; common pool problem